2017
DOI: 10.1002/2017gl075956
|View full text |Cite
|
Sign up to set email alerts
|

Rupture Process During the Mw 8.1 2017 Chiapas Mexico Earthquake: Shallow Intraplate Normal Faulting by Slab Bending

Abstract: A seismic source model for the Mw 8.1 2017 Chiapas, Mexico, earthquake was constructed by kinematic waveform inversion using globally observed teleseismic waveforms, suggesting that the earthquake was a normal‐faulting event on a steeply dipping plane, with the major slip concentrated around a relatively shallow depth of 28 km. The modeled rupture evolution showed unilateral, downdip propagation northwestward from the hypocenter, and the downdip width of the main rupture was restricted to less than 30 km below… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 47 publications
1
16
0
3
Order By: Relevance
“…Fault patches with >1-m slip can be divided into two along-strike segments, separated by the TFZ (Figure 3c). A large slip patch peaks at 55 km along strike at 30-km depth with maximum slip of 9.5 m, which is consistent with other slip models derived from the seismic data (Jiménez, 2018;Okuwaki & Yagi, 2017;Ye et al, 2017), but is shallower than the slip peak at 60-km depth in a slip model derived from tsunami data (Gusman et al, 2017). The breaking of this slip patch, spanning a depth range of 10-70 km, releases most of the seismic moment.…”
Section: Ffmsupporting
confidence: 84%
See 1 more Smart Citation
“…Fault patches with >1-m slip can be divided into two along-strike segments, separated by the TFZ (Figure 3c). A large slip patch peaks at 55 km along strike at 30-km depth with maximum slip of 9.5 m, which is consistent with other slip models derived from the seismic data (Jiménez, 2018;Okuwaki & Yagi, 2017;Ye et al, 2017), but is shallower than the slip peak at 60-km depth in a slip model derived from tsunami data (Gusman et al, 2017). The breaking of this slip patch, spanning a depth range of 10-70 km, releases most of the seismic moment.…”
Section: Ffmsupporting
confidence: 84%
“…Source inversion of a large earthquake is typically nonunique (Lay et al, 2010). Using the global seismic data, Okuwaki and Yagi (2017) found that the 2017 Chiapas earthquake mainly ruptured shallower than 50 km. However, a deep, major rupture located with a depth range of 40-60 km is inverted by fitting the tsunami data (Gusman et al, 2017).…”
Section: 1029/2018gl080009mentioning
confidence: 99%
“…The stress triggering relation between the foreshock sequence and the mainshock is usually attributed to static stress triggering, dynamic triggering, or aseismic transients such as slow slip or fluid flow. In the case of the Tehuantepec earthquake, several finite fault studies suggest that the principal slip zone extends over a depth range of 25 km (USGS finite fault model; Ye et al, 2017;Okuwaki & Yagi, 2017;Chen et al, 2018;. The static stress change induced by fault rupture drops significantly with distance and becomes negligible when the receiver fault is located over two times the rupture length away (Hill & Prejean, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…The kinematic rupture processes of the M 8.2 event are characterized by a unilateral northwestward rupture propagation and a principle slip zone deeper than 25 km (Chen et al, 2018;Okuwaki & Yagi, 2017;Ye et al, 2017;Zhang & Brudzinski, 2019). The kinematic rupture processes of the M 8.2 event are characterized by a unilateral northwestward rupture propagation and a principle slip zone deeper than 25 km (Chen et al, 2018;Okuwaki & Yagi, 2017;Ye et al, 2017;Zhang & Brudzinski, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The potential energy of slab pulling is very important to the subduction recycled back into the Earth's mantle (Schellart & Rawlinson, 2013). The seismicity and deformation associated with deeper zone along the slab interface are usually relatively small in magnitude or are in the oceanic region, resulting in most focal mechanisms of normal faulting earthquakes in intermediate depth being determined only from teleseismic data (e.g., Sarlis et al, 2018;Ye et al, 2017), which has lower sensitivity to the focal geometry, in particular of focal depth than geodetic data (Christensen & Ruff, 1985;Okuwaki & Yagi, 2017;Silwal & Tape, 2016). Therefore, the subduction structure in intermediate depth is not known as well as in shallow depth.…”
Section: Introductionmentioning
confidence: 99%